NEW METHODICAL APPROACHES TO DEFINITION HAEMOLYTIC AND LECITHINASE ACTIVITY OF PROTEUS - Yurchenko, L. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Determinated haemolitics and lecithinase activity 80 cultures of Proteus, abstracted from the different hearts of infection; the cultures from pathological material had greater haemolitics activity as compared relatively transmitters. A hard defined medium with properties swarming inhibition, which didn’t inhibition activity Proteus for haemolitics of erythrocytes, is developed. Dependences of haemolytic or lecithinase activity of Proteus from its finding in O- or the H-form not revealed.